The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/microorganisms9122463
|View full text |Cite
|
Sign up to set email alerts
|

Succession of Microbial Communities in Waste Soils of an Iron Mine in Eastern China

Abstract: The reclamation of mine dump is largely centered on the role played by microorganisms. However, the succession of microbial community structure and function in ecological restoration of the mine soils is still poorly understood. In this study, soil samples with different stacking time were collected from the dump of an iron mine in China and the physicochemical characteristics and microbial communities of these samples were comparatively investigated. The results showed that the fresh bare samples had the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In our research Bradyrhizobium was found in mature soil. In acid fresh mine soils, the iron/sulfur-oxidizers such as Acidiferrobacter and Sulfobacillus were reported [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our research Bradyrhizobium was found in mature soil. In acid fresh mine soils, the iron/sulfur-oxidizers such as Acidiferrobacter and Sulfobacillus were reported [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The belowground microbial functional diversity is determined by dynamic, multi‐level interactions occurring between soil microbes, plants (mainly roots and biomass), and other organisms (e.g., mezofauna and endophytes). The greater the plant biodiversity, the greater the heterogeneity of organic compounds delivered to the soil, leading to a higher taxonomic and functional diversity of soil microorganisms (Ezeokoli et al, 2020; Kane et al, 2020; Kompała‐Bąba et al, 2021; Woźniak et al, 2023; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about the pioneer microorganisms accompanying the early stages of vegetation succession on the coal mine heaps is scarce. Due to adverse physicochemical and nutritional conditions, the first colonizers are photosynthetic algae, chemolithotrophic and extremophilic bacteria, and methanogenic archaea (Bąba et al, 2016; Patel & Behera, 2011; Rahmonov et al, 2022; Wang et al, 2018; Woźniak, 2010; Woźniak et al, 2022; Zhang et al, 2021). Together with organic particles and seeds brought by the wind, animals, and humans, these pioneer microorganisms might be the source of soil organic carbon for saprophytic chemoorganotrophs (Li et al, 2015; Urbanová et al, 2011; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial communities present there are dominated by the genera Acidiferrobacter and Sulfobacillus. In old bare samples, Acidibacter, Metallibacterium, and Cyanobacteria are abundant, while the phylum Acidobacteriota prevails in the vegetated samples and promotes nutrient enrichment and plant growth significantly [13]. The assessment of the microbiological and chemical spatial distribution within two tailing basins from a tungsten mine has shown that the tailings sediments core microbiome contained members of the family Anaerolineacea and the following genera: Acinetobacter, Bacillus, Cellulomonas, Pseudomonas, Streptococcus, and Rothia [14].…”
Section: Introductionmentioning
confidence: 99%